Evaluating the efficacy and safety of rivaroxaban as a warfarin alternative in chronic thromboembolic pulmonary hypertension patients undergoing pulmonary endarterectomy: A randomized clinical trial - Saghar Barati; Hossein Amini; Zargham Hossein Ahmadi; Alireza Dastan; Babak Sharif Kashani; Raha Eskandari; Farzaneh Dastan (Revista Portuguesa de Cardiologia, 2023)
Background and aim: Chronic thromboembolic pulmonary hypertension (CTEPH) is caused by the obstruction of the main pulmonary artery due to thrombosis and vascular remodeling. Regarding the need for anticoagulant therapy in CTEPH patients, this study aimed to compare rivaroxaban with warfarin in terms of its efficacy and safety in patients undergoing endarterectomy surgery. Methods: The study was a parallel clinical trial in patients who underwent endarterectomy following CTEPH. A total of 96 patients were randomly selected and assigned to two groups: warfarin-treated (control) and rivaroxaban-treated (intervention). Patients were clinically assessed for re-thrombosis, re-admission, bleeding, and mortality in the first, third, and sixth months after surgery. Results: There was no significant difference in the occurrence of thrombosis between the two groups within the first, third-, and sixth-months post-surgery (p=0.52, 1, 0.38 respectively). Moreover, the mortality rate (p=0.9), bleeding rate (p=0.06), and re-admission rate (p=0.15) showed no significant differences between the two groups. Conclusion: Rivaroxaban may be as effective as warfarin in treating CTEPH patients after endarterectomy in the short term and can be used as an anticoagulant in these patients. However, studies with long-term follow-ups are needed to consolidate the strategy of treating these patients with rivaroxaban. Resumo: Introdução e objetivos: A hipertensão pulmonar tromboembólica crónica (HPTEC) é causada pela obstrução da artéria pulmonar principal devido a trombose e a remodelagem vascular. Relativamente à terapêutica anticoagulante em doentes com HPTEC, este estudo teve como objetivo comparar o rivaroxabano com a varfarina no que concerne à sua eficácia e segurança em doentes submetidos a cirurgia de endarterectomia. Métodos: O estudo consistiu num ensaio clínico paralelo em doentes submetidos a endarterectomia após HPTEC. Foram selecionados aleatoriamente 96 doentes e distribuídos por dois grupos: doentes tratados com varfarina (controlo) e doentes tratados com rivaroxabano (intervenção). Os doentes foram avaliados clinicamente para retrombose, reinternamento, hemorragia e mortalidade, ao primeiro, terceiro e sexto meses após a cirurgia. Resultados: Não se registaram diferenças significativas em relação à ocorrência de trombose entre os dois grupos após a cirurgia. (Valor p=0,52, 1, 0,38 respetivamente). Além disso, a taxa de mortalidade (Valor p=0,9), a taxa de hemorragia (Valor p=0,06) e a taxa de reinternamento (Valor p=0,15) não revelaram diferenças significativas entre os dois grupos. Conclusão: O rivaroxabano pode ser tão eficaz a curto prazo como a varfarina no tratamento de doentes com HPTEC após endarterectomia e pode ser utilizado como anticoagulante nestes doentes. No entanto, são necessários estudos de seguimentos a longo prazo para consolidar esta estratégia de tratamento com rivaroxabano.